Relationship between endocrine disrupting chemicals (phthalate metabolites, triclosan and bisphenols) and vitamin D in female subjects: An exploratory pilot study - Brennan, Edwina; Butler, Alexandra E.; Nandakumar, Manjula; Thompson, Kristie; Sathyapalan, Thozhukat; Atkin, Stephen L. (Chemosphere (Oxford), 2024)
Evidence suggests that endocrine disrupting chemicals (EDCs), commonly used in plastics and personal care products, may be associated with reduced levels of vitamin D. Therefore, this study examined the relationship between phthalate metabolites, 5-chloro-2-(2,4-dichlorophenoxy)phenol (triclosan; TCS) and bisphenols (BPs) with vitamin D3 (25(OH)D3) and active 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), and their relationship to calcium homeostasis. 57 female participants (age 31.8 ± 4.6 years; BMI 25.6 ± 3.7 kg/m2) were analyzed for urinary levels of phthalate metabolites, TCS and BPs, and serum levels of 25(OH)D3 and 1,25(OH)2D3, determined by isotope-dilution liquid chromatography tandem mass spectrometry. Serum calcium/calmodulin-dependent (CaM) associated proteins were determined by Slow Off-rate Modified Aptamer (SOMA)-scan. In the study cohort, 25(OH)D3 and 1,25(OH)2D3 levels were 22.9 ± 11.2 ng/mL and 0.05 ± 0.02 ng/mL, respectively: mono-3-carboxypropyl-phthalate (MCPP) correlated negatively with 25(OH)D3 (ρ = −0.53, p = 0.01). 28 of the 57 women recruited were 25(OH)D3 deficient, <20 ng/mL (50 nmol/L): in this group, mono-iso-butylphthalate (MiBP) and mono-butylphthalate (MBP) negatively correlated with 25(OH)D3; (ρ = −0.47, p = 0.049) and (ρ = −0.64, p = 0.005), respectively. EDCs did not correlate with 1,25(OH)2D3, measures of renal function or CaM proteins. These putative data indicate that MCPP is related to 25(OH)D3, while MiBP and MBP were related to vitamin D deficiency; however, no correlations were observed with TCS and BPs. No phthalate metabolites correlated with 1,25(OH)2D3, CaM associated proteins or renal function, suggesting that effects occur earlier in the vitamin D pathway and not through modulation of cellular calcium flux. The observed correlations are surprisingly strong compared to other predictors of 25(OH)D3, and larger studies adjusting for potential confounders are warranted. [Display omitted] •Phthalates are proposed to impact CYP enzymes involved in 1,25(OH)2D3 metabolism.•The relationship between phthalate metabolites and 25(OH)D3 in women was examined.•MCPP negatively correlated with 25(OH)D3 in the study cohort.•In deficient 25(OH)D3 women, MiBP and MBP negatively correlated with 25(OH)D3.•Observed correlations are remarkably strong compared to other predictors of 25(OH)D3.